2004
DOI: 10.1021/tx049836w
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme-Activated, Hypoxia-Selective DNA Damage by 3-Amino-2-quinoxalinecarbonitrile 1,4-Di-N-oxide

Abstract: The compound 3-amino-2-quinoxalinecarbonitrile 1,4-dioxide (4) displays potent hypoxia-selective cytotoxicity in cell culture. This compound is structurally similar to the known hypoxia-selective DNA-damaging agent tirapazamine (1, TPZ), but the ability of 4 to cause DNA damage under low-oxygen conditions has not previously been characterized. The results presented here provide the first evidence that 4 causes reductively activated DNA damage under hypoxic conditions. The findings indicate that one-electron re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 37 publications
1
55
0
Order By: Relevance
“…For example, various 1,2,4-benzotriazines, 34-40 quinoxaline 1,4-di- N -oxides (e.g. 5 ), 41-47 phenazine 5,10-di- N -oxides ( 6 ), 48-51 and imidazo[1,2-a]quinoxaline N -oxides ( 7 ) 52 exhibit hypoxia-selective cytotoxicity in preclinical tests. In some cases, the compounds also have been shown to display hypoxia-selective DNA-damaging properties analogous to tirapazamine.…”
Section: Introductionmentioning
confidence: 99%
“…For example, various 1,2,4-benzotriazines, 34-40 quinoxaline 1,4-di- N -oxides (e.g. 5 ), 41-47 phenazine 5,10-di- N -oxides ( 6 ), 48-51 and imidazo[1,2-a]quinoxaline N -oxides ( 7 ) 52 exhibit hypoxia-selective cytotoxicity in preclinical tests. In some cases, the compounds also have been shown to display hypoxia-selective DNA-damaging properties analogous to tirapazamine.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a recent study documented that during N!O reduction of QCT, ROS such as superoxide anion (O 2 À ), hydrogen peroxide (H 2 O 2 ), and hydroxyl radicals (HO ) are generated (Wang et al, 2016b). As already known, ROS generation and oxidative stress resulted from the reduction of QdNOs, which might result in wide damage such as apoptosis, and DNA, lipid and protein damage (Azqueta et al, 2007;Chowdhury et al, 2004;Wang et al, 2016a) in vivo or in vitro. During the past more than 10 years, there has been considerable focus on the potential of QdNOs to induce (Dai et al, 2015;Huang et al, 2010b;Li et al, 2015;Liu et al, 2012;Wang et al, 2015bWang et al, , 2016bWang et al, , 2015cYang et al, 2013bZhang et al, 2011Zhang et al, , 2013Zhang et al, , 2014Zhang et al, , 2015Zhao et al, 2013Zhao et al, , 2015Zou et al, 2009Zou et al, , 2011.…”
Section: Introductionmentioning
confidence: 95%
“…In addition, quinoxalines and their mono-and di-N-oxide derivatives display a broad range of biological activities [10] and quinoxaline di-N-oxides are known to undergo bioreductions under hypoxia causing DNA damage [26][27][28] and likely other cellular damage.…”
Section: General Backgroundmentioning
confidence: 99%
“…Specific derivatives also show selective cytotoxicity against hypoxic cells present in solid tumors [21]. Furthermore, recent studies have demonstrated that quinoxaline 1,4-di-N-oxides are endowed with antimycobacterial, antiprotozoal [22,23], anticandida [24,25] activities and mutagenic properties [26][27][28], depending on specific chemical features.…”
Section: Introductionmentioning
confidence: 99%